2013
DOI: 10.1161/hypertensionaha.113.01028
|View full text |Cite
|
Sign up to set email alerts
|

p53 Mediates Autophagy and Cell Death by a Mechanism Contingent On Bnip3

Abstract: Abstract-Myocardial ischemia and angiotensin II activate the tumor suppressor p53 protein, which promotes cell death.Previously, we showed that the Bcl-2 death gene Bnip3 is highly induced during ischemia, where it triggers mitochondrial perturbations resulting in autophagy and cell death. However, whether p53 regulates Bnip3 and autophagy is unknown. Herein, we provide new compelling evidence for a novel signaling axis that commonly links p53 and Bnip3 for autophagy and cell death. p53 overexpression increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 33 publications
3
58
0
Order By: Relevance
“…Moreover, Bnip3 can promote autophagy/mitophagy in certain cells; however, this property of Bnip3 is obscure and likely occurs in a cell-and context-specific manner, given that we and others have found that Bnip3 can promote maladaptive autophagy, resulting in cell death (10,12,13).…”
Section: Significancementioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, Bnip3 can promote autophagy/mitophagy in certain cells; however, this property of Bnip3 is obscure and likely occurs in a cell-and context-specific manner, given that we and others have found that Bnip3 can promote maladaptive autophagy, resulting in cell death (10,12,13).…”
Section: Significancementioning
confidence: 90%
“…Postnatal rat cardiac myocytes were isolated from 1-to 2-d-old Sprague-Dawley rats and subjected to primary culture as described previously. Cells were treated with DOX (5 or 10 μM; Pfizer) for 18 h. Cells were infected with adenoviruses encoding Bnip3 shRNA or a carboxyl terminal domain mutant of Bnip3 defective for mitochondrial targeting, designated Bnip3ΔTM, as reported previously (10,15,16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that in late hypoxia, though HIF-1α began to decline, the apoptosis-inducing factor BNIP3, a target gene of HIF-1α, also known as the target gene of miR-210 (49), was strengthened. This might be because p53 (50) activation induced a BNIP3 increase in late hypoxia. Except that miR-210 could suppress local hypoxia group.…”
Section: Mir-210 Alleviated Hypoxia-induced Cell Injury and Apoptosismentioning
confidence: 99%